Adrift in the world of therapeutic apheresis: One center's experience in using arterio-venous fistulas during apheresis procedures. Issue 2 (October 2016) - Larson, Jennifer
Abstract: Therapeutic plasma exchange (TPE) is often an isolated specialty with very little research, especially in regard to the mode of access. This lack of information drove this attempt at reviewing the use of arterio-venous fistulas (AVF) in TPE, and specifically the issue of monitoring the accesses patency. Using a Transonic®, we attempted to obtain a reading, using the Spectra Optia™ on a patient's access. Unfortunately, due to the limitations of the equipment, we were unable to get a reading. Our conclusion is that we will have to monitor using other approaches, such as physical assessment and ultrasound.